2016
DOI: 10.1039/c6ra23092j
|View full text |Cite
|
Sign up to set email alerts
|

Lineariifolianoids I–L, four rare sesquiterpene lactone dimers inhibiting NO production from Inula lineariifolia

Abstract: Four unsymmetrical sesquiterpene lactone dimers were isolated from Inula lineariifolia. The absolute configurations of 1 and 2 were established by X-ray crystallographic analyses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…The studied species are rich in secondary compounds such as avonoids, sesquiterpenes and essential oils. [35][36][37][38][39][40][48][49][50] In the case of D. viscosa it has been reported that the concentration of leaf exudate phenolics increases under water stress. 50 In a recent work, Kheyar-Kraouche et al 19 study by HPLC-MS the composition and antioxidant activity of an ethanolic extract of D. viscosa leaves, identifying phenolic acids, avonoids, terpenoids and one lignan.…”
Section: Electrochemical Responsementioning
confidence: 99%
See 1 more Smart Citation
“…The studied species are rich in secondary compounds such as avonoids, sesquiterpenes and essential oils. [35][36][37][38][39][40][48][49][50] In the case of D. viscosa it has been reported that the concentration of leaf exudate phenolics increases under water stress. 50 In a recent work, Kheyar-Kraouche et al 19 study by HPLC-MS the composition and antioxidant activity of an ethanolic extract of D. viscosa leaves, identifying phenolic acids, avonoids, terpenoids and one lignan.…”
Section: Electrochemical Responsementioning
confidence: 99%
“…The voltammetric method exploits the electroactive character of polyphenolic compounds, (lignins, avonoids, avonols, avones, ..) abundantly represented in the leaves of the tribe. [35][36][37][38][39][40] Most of these components display well-known oxidations of o-catechol units to the corresponding oquinones highly sensitive to the overall molecular structure. [20][21][22][23][30][31][32][33][34]41,42 Ultimately, the current work was aimed to provide an analytical tool to be used in the botanic science frame to acquire 'direct' mechanistic information on ROS reactivity and its relation with biochemical processes that is unavailable from the usual HPLC methodologies.…”
Section: Introductionmentioning
confidence: 99%